Does Entrepreneurship Supply Chain Management Mediate the Effect of VOE Resources and Social Capital to Performance of Craftsmen? - Sinarwati, Ni Kadek; Marhaeni, AAIN; Utama, Suryana I Made; Budi, Made Kembar Sri (International Journal of Supply Chain Management, 2020)
Sustainable Development Goals aims to reduce inequality, however, this problem still occurs in Bali Province. Data from its Industry showed a gap in SME performance between cities, with the lowest performance of MSE in Karangasem Regency. The objective of this research was to analyze: the effect of Village Own Enterprise (VOE) resources and social capital to entrepreneurship and performance of craftsmen. Data used were quantitative and qualitative collected through observation, and in-depth interviews, with the SEM-PLS program used for its analyzes. The results show that the effect of VOE resource is positive but insignificant to entrepreneurship of craftsmen, while social capital is positive and significant. Furthermore entrepreneurship does not mediate the effect of VOE resources on performance, while entrepreneurship mediates the effect of social capital. The suggestion of this research were to VOE management in order to more introduce the existence of VOE, subsequent researchers need to add external variable that possible influence the performance of craftsmen for example government policy.